Coordination Behaviour of HerbicidalSchiff Bases Derived From 2-Amino-6-Ethoxybenzothiazole toward Copper (II) - Sinha, A.I.P.; Bala, Manju (Asian Journal of Chemistry, 2010)
The copper (II) chloride complex of 2-N-(salicylaldimine)-6-ethoxybenzothiazole (L1), 2-N-(2´-hydroxy-3´ -methoxybenzaldimine)-6-ethoxybenzothiazole (L2), 2-N-(2´-hydroxy-1´-napthaldimine)-6-ethoxybenzothiazole (L3), 2-N-(2´-furancarboxaldimine)-6-ethoxybenzothiazole (L4), and 2-N-(2´-thiophenecarboxaldimine)-6-ethoxybenzothiazole (L5) have the stoichiometry [Cu(L1)(H2O)]Cl2, [Cu(L2)2(H2O)2]Cl3, [Cu(L3)(H2O)]Cl2, (Cu(L4)2]Cl2·2H2O and [Cu(L5)2]Cl2·2H2O, respectively_ The complex compounds have been isolated and characterised by elemental analysis, electrical conductivity, magnetic measurements, and infrared spectral measurements.